Short and Intense Tailor-Made Notched Music Training against Tinnitus: The Tinnitus Frequency Matters - Teismann, Henning (Public Library of Science, 2011)
Tinnitus is one of the most common diseases in industrialized countries. Here, we developed and evaluated a short-term (5 subsequent days) and intensive (6 hours/day) tailor-made notched music training (TMNMT) for patients suffering from chronic, tonal tinnitus. We evaluated (i) the TMNMT efficacy in terms of behavioral and magnetoencephalographic outcome measures for two matched patient groups with either low (≤8 kHz, N = 10) or high (>8 kHz, N = 10) tinnitus frequencies, and the (ii) persistency of the TMNMT effects over the course of a four weeks post-training phase. The results indicated that the short-term intensive TMNMT took effect in patients with tinnitus frequencies ≤8 kHz: subjective tinnitus loudness, tinnitus-related distress, and tinnitus-related auditory cortex evoked activity were significantly reduced after TMNMT completion. However, in the patients with tinnitus frequencies >8 kHz, significant changes were not observed. Interpreted in their entirety, the results also indicated that the induced changes in auditory cortex evoked neuronal activity and tinnitus loudness were not persistent, encouraging the application of the TMNMT as a longer-term training. The findings are essential in guiding the intended transfer of this neuro-scientific treatment approach into routine clinical practice.